Atividade citotóxica do óleo essencial de Lippia spp. frente a células da linhagem A549 de carcinoma de pulmão humano - Almeida, Patrícia de Oliveira Santos (2016)
The lung carcinomas stand out as a major public health problem, therefore, are among the leading causes of cancer death worldwide. They are classified into two major histological groups: small cell lung carcinome (SCLC) and non small cell lung carcinoma non (NSCLC). In the search for novel therapies, many natural products derived from plants and other organisms has been studied for use as a source for the development of chemotherapeutic agents used in the treatment of various cancers, including carcinomas of the lung. In this context, the essential oils is part of medicinal plants produced by such as the genus Lippia that have many therapeutic properties, among them, antimicrobial, anti-inflammatory and antiproliferative. This study proposes to investigate the cytotoxic activity of essential oils of different species and genotypes of the genus Lippia plants. the Active Germplasm Bank of the Federal University of Sergipe (UFS) located at the Experimental Farm "Rural Campus of the UFS," which have varied chemical composition. For this A549 cells (lung carcinoma) were treated with increasing concentrations (20-160 / mL) essential oils Lippia gracilis (genotypes 106 and 110) of Lippia alba (genotypes 13:57) and Lippia sidoides (genotypes 102 and 104) during the 24 hour interval. Cytotoxicity of these essential oils was determined by the MTT colorimetric method. The absorbance values obtained in the treatments were normalized to the untreated cells and used to calculate IC50 values by regression analysis. IC50 values of 75.42 and 158.6 ug / ml were obtained for the LG-106 and LG-110 genotypes, respectively. For LS-102 and LS-104 genotypes IC50 were respectively 97.93 and 150.70 mg / mL and LA-13 and LA-57 genotypes these values were 86.14 and 70.34 mg / mL . Microscopic analysis of cells stained by hematoxylin-eosin showed morphological changes, including condensation of cytoplasm, chromatin condensation and nuclear fragmentation induced by all genotypes. These results suggest that the cytotoxic activity presented by the essential oils of Lippia on A549 lineage cells involves induction of programmed cell death. Therefore, it is concluded that these oils represent a promising source compounds for the development of new anti-tumor therapies.